1973
DOI: 10.1159/000240557
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pancreatic α-Amylase in the Neonatal Mouse

Abstract: The decrease in specific activity of mouse pancreatic α-amylase occurring at parturition is associated with changes in the morphological fine structure of the acinar cells, as evidenced by a decrease in the number of zymogen granules per cell and an increase in the rough endoplasmic reticulum. Following parturition there is a rapid increase in the synthesis of both amylase and total protein, with a selective increase in amylase synthesis during the first 24 hours. Metabolic requirements for in vitro secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…Concentrations of catecholamines were optimal for stimulation of secretion and increased cyclic A M P levels in mature tissues as verified in previous studies (1 1,12,20). At the end of the incubation period, the medium was removed and frozen for subsequent determination of protein content and amylase activity.…”
Section: Animals and Tissue Preparationsupporting
confidence: 57%
See 1 more Smart Citation
“…Concentrations of catecholamines were optimal for stimulation of secretion and increased cyclic A M P levels in mature tissues as verified in previous studies (1 1,12,20). At the end of the incubation period, the medium was removed and frozen for subsequent determination of protein content and amylase activity.…”
Section: Animals and Tissue Preparationsupporting
confidence: 57%
“…Similarly, in studies of secretory function in developing pancreas, other workers (1,14) have shown an incremental response to carbamylcholine stimulation from fetal day 1 3 to the third day of life. In their experiments and others (7), however, ontogeny of receptors was not studied; and no such data are yet available for the parotid gland.…”
Section: Discussionmentioning
confidence: 72%
“…The physiological media tor for the in vivo hormone effects remains to be identified. Interes• tingly, in the newborn pancreas insulin together with glucose were found obligatory for normal func• tion (Albritton, Koops, Hurwitz and Kretchmer 1973;Cheneval and Johnstone 1976). This could indicate that exocrine cells respond directIy to insu• lin and eventually express insulin receptors only during growth and development and later only uno der pathological conditions.…”
Section: )_mentioning
confidence: 99%